Supplies for Type 1 Diabetes management during COVID-19 social distancing in Brazil - Leão Reis, Aline; Nogueira Berino, Talita; da Cruz e Silva, Aline Daniela; de Lima Carvalhal, Manuela Maria; Dias Kikuchi, Jeane Lorena; Correia Uliana, Gabriela; Lopes Gomes, Daniela (O Mundo da Saúde, 2022)
This study analyzed socioeconomic factors related with the acquisition of supplies for blood glucose management by people with Type 1 Diabetes Mellitus during social distancing due to the COVID-19 Pandemic in Brazil. This was a cross-sectional study with data collected during 21 days in July 2020, by an online form on socioeconomic data and acquisition of supplies for glycemic monitoring. This research applied Pearson’s Chi-Squared test with adjusted residual analysis (p<0.05). 472 adults of both sexes participated. Relationships were found between the type of device used for blood glucose monitoring (glucometer or Flash system) and income (p<0.000), education (p=0.007), macro-regions (p=0.049), and type of city (p=0.043); between insulin acquisition and income (p<0.000), macro-region (p=0.027) and type of neighborhood (p=0.003); between acquisition of reagent strips and income (p<0.000); between acquisition of lancets and income (p=0.001), type of city (p=0.035) and neighborhood (p=0.010); between the use of Flash System and income (p<0.000) and type of neighborhood (p=0.006). The results expose the social inequalities in the acquisition of supplies for blood glucose management by people with Type 1 Diabetes during the Pandemic in Brazil.